Grace Kennison: capstone - Kennison, Grace, artist (Colorado State University. Libraries, 2018)
The artist's statement: As an artist I have become interested in exploring the feminine experience and feminist theory in ways that speak authentically to living and growing as a woman. I have creatively explored feminist discourse for the past three years parallel to my concentration in drawing and find it fulfilling to work within a feminist consciousness and analyze modern dialect alongside drawing. Artistically processing and rendering my findings within womanhood and women's studies improves my personal life and my artistic sensibilities, giving purpose to my work and clarity to my life. Being able to balance between play and critical thought is essential to my personal feminist practice and that is reflected well in my drawings. Stylistically, my drawings are playful and childlike in ways that suit my more complex conceptual roots. As someone who is a visual learner, transforming menacing feminist frameworks into a more tangible and aesthetically approachable works of art helps me engage with and enjoy them on a deeper creative level. Conceptually, I have dealt with a spectrum of material including Audre Lorde's work in Sister Outsider including the notion of erotic power, sexualization of young girls and hypersexualization of women, Judith Butler's notion of gender performance, and the writings of Patricia Hill Collins, bell hooks, and other feminist authors.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing